Gender, Sexuality and Emotion in Visual Representations of Sweden Joining NATO - Emma Rosengren (Journal of Autonomy and Security Studies, 2023)
This research note introduces gender and feminist theory as important tools for understanding international relations (IR), and uses snapshots from my ongoing research project on gender and disarmament in Swedish security policy during the post-Cold War period to exemplify what feminist contributions to the field can look like. Analyzing media visuals about Sweden’s relationship with NATO during 2022–2023, I argue that such sources draw on well-known societal stereotypes about, for example, gender to make sense to their audiences. The visuals included in this study contribute to destabilize associations between security policy, national identity and masculinity from Cold War Sweden by portraying Swedish politicians as female brides ready to marry male NATO representatives and thereby gain protection within what has previously been conceptualized as a gendered NATO family. Both human bodies and emotions related to fear contribute to make meaning about such representations.